Analysis of the Effectiveness of Internal Control Systems for Receivables to Minimize Uncollectible Receivables at Pt. Abx - Trivena Oktariani; Adam Zakaria; Choirul Anwar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effectiveness of PT ABX's internal control system for accounts receivable in minimizing uncollectible accounts. PT ABX is a consumer goods distribution company that conducts large-scale credit sales. Despite having implemented standard operating procedures (SOP) for accounts receivable management, the company experienced a significant increase in uncollectible accounts receivable from 2021 to 2023, indicating weaknesses in the implementation of the existing internal control system. Employing a descriptive qualitative approach, this study uses the case study method and references the COSO framework, consisting of five components: control environment, risk assessment, control activities, information and communication, and monitoring. Data were collected through in-depth interviews, direct observations, and document reviews and were analyzed using NVivo 12 Plus software. The results indicate that, although the control structure has been designed, it has not yet been implemented optimally. Various challenges were identified, including weak segregation of duties, insufficient customer risk assessment, limitations in the information system, and a lack of integrated monitoring. The study recommends improving customer risk analysis, the accounts receivable information system, and human resource training. It also recommends strengthening data-driven monitoring and evaluation. These findings emphasize that internal control system effectiveness depends not only on the existence of written procedures, but also on consistent implementation and ongoing cross-functional coordination.